Gender Disparities in Child Labor and Economic Development in Nepal - Karna, Poonam Kumari Labh (Lembaga Yasin AlSys, 2025)
Child labor continues to be a significant problem in Nepal, particularly in rural areas where poverty and restricted access to education contribute to the perpetuation of the cycle of economic deprivation. The purpose of this study is to investigate the gender differences in child work and the consequences such differences have for the improvement of Nepal's economy. Utilizing information obtained from the Nepal Living Standards Survey (NLSS) conducted in 1995, this study illustrates the numerous ways in which gender influences decisions about child work and schooling. Particular attention is paid to the role that poverty, access to credit, and household characteristics have in these decisions. As a result of the findings, it appears that girls are more likely to be engaged in household work and less likely to attend school in comparison to males. This has ramifications for Nepal's economic development in the long run. In order to address these discrepancies and to promote gender equality in school and the labor market, policy solutions are presented throughout this article.